2020
DOI: 10.1021/acsabm.0c01221
|View full text |Cite
|
Sign up to set email alerts
|

Gallium Complex-Functionalized P4HB Fibers: A Trojan Horse to Fight Bacterial Infection

Abstract: Broadband administration and overuse of conventional antibiotics contribute to antibiotic resistance, demanding for alternative strategies. Metal ions, among them gallium (Ga), gained increasing interest as antibacterial agents. Ga can be complexed in a protoporphyrin ring (GaPPIX) and thereby shares similarities with the heme molecule and functions as a Trojan horse that is internalized by bacteria. Different to iron in heme, Ga interferes with the metabolism, induces bacterial death, and can therefore be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…No toxicity to human dermal fibroblasts was observed. This indicates that LM-based antimicrobial fabrics are expected to be an antimicrobial product for inhibiting skin trauma [ 113 ].…”
Section: Antibacterial Application Of Lm-based Materialsmentioning
confidence: 99%
“…No toxicity to human dermal fibroblasts was observed. This indicates that LM-based antimicrobial fabrics are expected to be an antimicrobial product for inhibiting skin trauma [ 113 ].…”
Section: Antibacterial Application Of Lm-based Materialsmentioning
confidence: 99%
“…This includes surpassing the antimicrobial rate of Ti-6Al-4V by a substantial margin. The mechanism underlying the observed antibacterial effect in Ga-containing alloys is hypothesized to involve a “Trojan horse” strategy of bacterial inhibition, which has been extensively studied [ 53 , 54 , 55 , 56 ]. Gallium ions (Ga 3+ ) contain an analogous electron affinity, ionisation potential, and ionic radius with ferric ions (Fe 3+ ), potentially leading them to be mistaken for Fe 3+ and binding strongly to iron-binding proteins crucial in bacterial metabolic and signalling processes [ 17 , 50 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial cells produce siderophores to uptake iron, and Ga 3+ competes with Fe 3+ for binding to siderophores and vital proteins and enzymes [ 53 ]. Gallium is not redox-active; when bound to iron-binding proteins, it can disrupt various iron-dependent redox pathways, thereby compromising bacterial cell function and survival [ 53 , 54 , 56 ]. By comparing their antibacterial efficacy, it becomes evident that Ti-33Nb-3Ga and Ti-33Nb-5Ga possess a superior capacity to inhibit biofilm formation, consequently reducing the likelihood of implant failure and the need for revision surgeries in comparison to the currently utilized Ti-6Al-4V.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial mechanism of gallium has been researched extensively [17,[51][52][53] and is theorised to employ a "Trojan horse" strategy of bacterial inhibition. Gallium ions (Ga 3+ ) possess an analogous ionic radius, electron affinity, and ionisation potential to that of ferric ions (Fe 3+ ), and may therefore be mistaken for Fe 3+ and bind strongly with ironbinding proteins involved in the metabolic and signalling processes of bacteria [17,51,54].…”
Section: Antimicrobial Mechanism Of Galliummentioning
confidence: 99%
“…Siderophores are produced by bacterial cells and possess iron uptake systems, where Ga 3+ competes with Fe 3+ to bind to siderophores and essential enzymes and proteins [17]. Gallium is not redox-active, and when bound with iron-binding proteins can inhibit various iron-dependent redox pathways, and ultimately the function and subsistence of the bacterial cell [17,52,53]. Various studies have demonstrated gallium-to-siderophore binding ability.…”
Section: Antimicrobial Mechanism Of Galliummentioning
confidence: 99%